The Judicial Implementation of the Provisions of Corporate Crimes in Saudi Law - al-Subaie, Mohammed bin Fahed (Journal of Economic, Administrative and Legal Sciences, 2019)
This study aimed to identify the judicial implementation of the provisions of corporate crimes in Saudi law and determine the objectives of judicial execution and the competent authority in adjudicating the disputes of commercial companies and the role of lawyers in the trial proceedings in the crimes of commercial companies. Moreover, this study aimed at how to achieve justice in commercial courts. The researcher followed the descriptive method in this study as it has included all texts related to the activities and commercial relations contained in the current regulations. The results of the study reached several results, the most important of which are: The jurisdiction over the consideration of commercial disputes in the Kingdom has passed several stages, but in the recent past it is divided into two parts: the first is the Diwan of Grievances; the second is the committees with jurisdiction. However, Ombudsman for Commercial Disputes. As well as the judicial environment in the Kingdom is living a significant positive movement, especially in the legislative and executive aspects, and the non-unification of commercial judicial bodies in one hand led to duplication of the judiciary and resulted in the presence of more than one body charged with separating with the differentiation of competencies and their overlap in one conflict. The study recommended the need to unify the Saudi commercial judicial bodies in one jurisdiction, the commercial courts of the public judiciary, and rely on modern techniques of telecommuting methods to provide easy communication with lawyers.